Childhood asthma in low and middle-income countries: Where are we now?. (August 2019) - Fischer, Gilberto Bueno; Sarria, Edgar E.; Camargos, Paulo; Mocelin, Helena Teresinha; Soto-Quiroz, Manuel; Cruz, Alvaro A.; Bousquet, Jean; Zar, Heather J.
Summary: Pediatric asthma has been increasing in LMICs (Low Middle-Income Countries), leading to an important burden for both children and national health systems. Implementing measures to achieve control are influenced by the degree of organization health systems have, the availability and affordability of essential asthma medications, and the effective implementation of asthma programs and asthma guidelines. In this review authors give an updated view of the current situation of these components of asthma management in LMICs.